Specificity of weightlifting bench exercises in kayaking sprint performance: A perspective for neuromuscular training - Romagnoli, Cristian; Gatta, Giorgio; Lamouchideli, Niloofar; Bianco, Antonino; Loddo, Stefano; Alashram, Anas R.; Bonaiuto, Vincenzo; Annino, Giuseppe; Padua, Elvira (Frontiers in Physiology, 2022)
Several studies showed significant differences between bench lift exercises without investigating which is more related, in biomechanical and neuromuscular terms, to improve the sprint flatwater kayak performance. This study aims to compare the power-load and velocity-load neuromuscular parameters performed in prone bench pull (PBP) and bench press (BP) exercises to identify which of them meet the gesture specificity in sprint flatwater kayak performance. Ten elite kayakers participated in this study. Power-load, velocity-load relationships, the maximum dynamic strength, and the kayak sprint performance test were assessed. The power-load and velocity-load relationships showed significant differences between the PBP and BP for each considered load. The kayakers showed a significant correlation between maximum power performed on the PBP and the maximum velocity reached in the kayak sprint (r=0.80,p<0.01) and the stroke frequency (r=0.61,p<0.05). Conversely, the maximum power performed on the BP did not show any correlation with the kinematic parameters analyzed. In addition, the maximum dynamic strength in the PBP and BP did not show any correlation with the maximum velocity and stroke frequency. Furthermore, no significant difference was observed in both the bench exercises for the maximum dynamic strength (p>0.05). The results of this study suggest that the maximal muscular power expressed in PBP exercise only seems to be more specific in kayak velocity performance compared with maximal dynamic strength and with all dynamic parameters recorded in the BP. This will allow coaches and trainers to use specific bench exercises for specific neuromuscular kayakers’ adaptations in the whole competitive season.